School EFL Teachers’ Research Identity Construction in the Chinese University–School Community - Wang, Xuemei; He, Yanhua (Frontiers in Psychology, 2022)
Despite a relatively large number of studies on teachers’ identity development in the University-School community, few studies have explicitly focused on school EFL teachers’ research identity construction. This study adopts the Activity Theory and examines three English as a foreign language (EFL) teachers from three middle schools in a University–School community in China. It investigates how three teachers constructed their research identity and what factors influenced the construction of their identities within the University–School activity system from the dual perspectives of the school and university teachers. Data are collected through semi-structured narrative interviews, triangulated by documents such as meeting minutes, and then analyzed by NVivo 12. The findings of this study show that (1) the University–School collaborative program helps form a University–School community of both teaching and research; (2) in this community, school EFL teachers continuously construct their identities in a spiral process of “practitioner” and “researcher”; (3) it highlights the internal factors containing the research experience and the stage of career and the external factors including the curriculum reform context and the communication in the community. The findings carry important implications for school EFL teachers’ research identity construction and professional development in the University–School cooperation.